Protocol for Sampling Sequential Fin Spine Growth Intervals for Isotope Analysis in the Atlantic Bluefin Tuna - Luque, Patricia Lastra; Sakai, Saburo; Murua, Hilario; Arrizabalaga, Haritz (Frontiers in Marine Science, 2020)
Background: Micromilled fish otoliths (ear bones) have been widely used for stable oxygen (δ18O) and carbon (δ13C) isotope analysis. The first dorsal fin spine is routinely used for ageing in the eastern Atlantic bluefin tuna (ABFT) population; however, stable isotope analysis remains unapplied in this hard structure. The objective of the present protocol is to achieve a sequential sampling of growth layers in the ABFT fin spine at high spatial resolution and along growth trajectory for stable isotope analysis. Methods: We used a micromilling and micro-powder collecting technique for sequentially sampling annual growth layers of the fin spine bone collected from freshly caught ABFT. We assessed the carbonate content and the optimal drilling amount to ensure enough powder quantity was recovered from each annual growth band to accommodate accurate measurement of the δ18O and δ13C values. Results: The optimal drilling path included 20 drilling lines in 49 µm, with 400 µm depth and 900 µm-line width, which represents a time resolution of about 2.5 months. The minimum powder quantity required from each annual growth layer for δ18O and δ13C isotope analysis was approximately 180 µg because the carbonate contents in the fin spine powder was 5-6 %. The δ18O profile assayed in the last growth intervals coincide with the surface δ18Oseawater for the southern west waters off the Norwegian coast, where the tuna was caught. The fluctuating pattern in the second growth interval may reflect certain fidelity to the Norwegian SE and Swedish SW coast and/or otherwise to the US west coast. The δ13Cspine displayed a larger temporal variability along the growth transect that may be explained by several factors including differences in habitat use, behavior, and even trophic level. Conclusion: Based on the result obtained, we present an optimal standard protocol for the sampling of sequential, annually formed growth layers in the fin spine bone for stable isotope analysis using the micro-milling as a high precision technique. This protocol is particularly useful in endangered and/or protected species for which fin spines represent a non-lethal alternative to otolith, bringing new research avenues to improve their management and conservation.